2012
DOI: 10.1136/jech-2011-200478
|View full text |Cite
|
Sign up to set email alerts
|

Community advocacy groups as a means to address the social environment of female sex workers: a case study in Andhra Pradesh, India

Abstract: BackgroundTo examine the association between the presence of community advocacy groups (CAGs) and female sex workers' (FSWs) access to social entitlements and outcomes of police advocacy.MethodsData were used from a cross-sectional survey conducted in 2010–2011 among 1986 FSWs and 104 NGO outreach workers from five districts of Andhra Pradesh. FSWs were recruited using a probability-based sampling from 104 primary sampling units (PSUs). A PSU is a geographical area covered by one outreach worker and is expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…Importantly, findings from the current study underline the importance of collective efficacy as strategy to promote HIV prevention interventions, especially in challenging settings as evidenced in the Aastha project and elsewhere 22 23. These results parallel the previous research findings in Karnataka where it was shown that a higher degree of collectivisation was associated with increased knowledge and condom use by FSWs,5 and in Andhra Pradesh, where it was evident that higher degree of community mobilisation increased condom use and reduce violence 1 22…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Importantly, findings from the current study underline the importance of collective efficacy as strategy to promote HIV prevention interventions, especially in challenging settings as evidenced in the Aastha project and elsewhere 22 23. These results parallel the previous research findings in Karnataka where it was shown that a higher degree of collectivisation was associated with increased knowledge and condom use by FSWs,5 and in Andhra Pradesh, where it was evident that higher degree of community mobilisation increased condom use and reduce violence 1 22…”
Section: Discussionmentioning
confidence: 65%
“…All the researchers had a bachelor's degree in either sociology or statistics. The survey instrument commonly developed by Avahan for its sites in India1 17 22 23 was modified locally to add a few questions that are relevant to the local context. The survey instrument was then translated from English to Hindi.…”
Section: Methodsmentioning
confidence: 99%
“…Both abuse by state-actors,and systemic lack of response to sex workers’ reports of violence foster impunity that perpetuates violence, and conveysan acceptability of violence towards sex workers.Failure to hold perpetrators accountable isa policy of tolerance for abuse. 32 Even in criminalized regimes, sex worker partnerships with legal and criminal justice sectors can have a significant impact on impunity.In Poland 32 and Andhra Pradesh, India, 109 sex workers have led change in partnership with police through training on sex worker rights and establishing safe reporting of abuse. These partnerships exemplify meaningful steps towards dismantling impunity.…”
Section: Evidence-based Reform: the Human Rights Framework For Changementioning
confidence: 99%
“…Literature suggests that developing countries may continue to establish similar kind of groups as one of the structural intervention approaches to combat HIV/AIDS. Literature on the role of SHGs in generating awareness and exposure to HIV/AIDS prevention interventions among FSWs in developing country like India is limited, with focus on community mobilization, social capital and social support [21] [23].…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, the studies emphasize the importance of SHGs in empowering FSWs and in reduction the risk & vulnerability to STI/HIV [19] [20] [21]. The additional benefit is that such group can play an important role in addressing HIV prevention behaviors such as safe sex practices, HIV status disclosure and condom use to decrease the spread of the disease [22].…”
Section: Introductionmentioning
confidence: 99%